Birth weight, Early Life Course BMI, and Body Size Change: Chains of Risk to Adult Inflammation? - Goosby, Bridget J. (Soc Sci Med, 2015)
This paper examines how body size changes over the early life course predict high-sensitivity C-reactive protein in a U.S. based sample. Using three waves of the National Longitudinal Study of Adolescent Health (Add Health), we test the chronic disease epidemiological models of fetal origins, sensitive periods, and chains of risk from birth into adulthood. Few studies link birth weight and changes in obesity status over adolescence and early adulthood to adult obesity and inflammation. Consistent with fetal origins and sensitive periods hypotheses, body size and obesity status at each developmental period, along with increasing body size between periods, are highly correlated with adult CRP. However, the predictive power of earlier life course periods is mediated by body size and body size change at later periods in a pattern consistent with the chains of risk model. Adult increases in obesity had effect sizes of nearly .3sd, and effect sizes from overweight to the largest obesity categories were between .3–1sd. There was also evidence that risk can be offset by weight loss, which suggests that interventions can reduce inflammation and cardiovascular risk, that females are more sensitive to body size changes, and that body size trajectories over the early life course account for African American-and Hispanic-white disparities in adult inflammation.